CULTURAL ASTRONOMY OF RYUKYU ISLANDS, SOUTHERN JAPAN - Goto, Akira (The Indonesian Journal of Social Studies, 2025)
The Japanese archipelago extends over 20 degrees of latitude from north to south. The Ainu culture flourished in Hokkaido at the northern end, and the Ryukyu culture flourished in Okinawa at the southern end. The Ryukyu Islands are located at the intersection of the Japanese archipelago, the Chinese mainland, Taiwan, and the islands of Southeast Asia. From prehistoric to historical times, cultures flowed in from various directions. Furthermore, the region's religion was characterized by shamanism overseen by female priests, and independent kingdoms formed. This paper aims to elucidate Ryukyuan cultural astronomy in this geographically and culturally diverse context. This section's methodology involves interpreting astronomical phenomena discernible from folklore, myths, and rituals using astronomical data and celestial simulations. This paper introduces the unique aspects of archaeoastronomy and cultural astronomy in Okinawa, focusing on monuments such as the Sun Stone, the Utaki shrines, and star-observing stones. In addition to the importance of the sun, this paper shows that the Pleiades and Orion's Belt are the most conspicuous in the Ryukyu Islands. The paper also discusses the local names and legends of southern stars, such as the Southern Cross. Other notable constellations in Okinawa include Centaurus, Scorpio, Sagittarius, and α and β Centauri. There is also a unique tale about the origin of "star sand." This paper then provides an overview of cultural astronomy related mainly to southern stars, focusing on the Ryukyu Islands.